Serum metabolomic signatures of patients with rare neurogenetic diseases: an insight into potential biomarkers and treatment targets - Wijekoon, Nalaka; Gonawala, Lakmal; Ratnayake, Pyara; Sirisena, Darshana; Gunasekara, Harsha; Dissanayake, Athula; Amaratunga, Dhammika; Steinbusch, Harry W. M.; Hathout, Yetrib; Hoffman, Eric P.; Dalal, Ashwin; Mohan, Chandra; et al. (Frontiers in Molecular Neuroscience, 2025)
IntroductionTo further advance our understanding of Muscular Dystrophies (MDs) and Spinocerebellar Ataxias (SCAs), it is necessary to identify the biological patterns associated with disease pathology. Although progress has been made in the fields of genetics and transcriptomics, there is a need for proteomics and metabolomics studies. The present study aimed to be the first to document serum metabolic signatures of MDs (DMD, BMD, and LGMD 2A) SCAs (SCA 1-3), from a South Asian perspective.MethodsA total of 28 patients (SCA 1-10, SCA 2-2, SCA 3-2, DMD-10, BMD-2, LGMD-2) and eight controls (aged 8–65 years) were included. Metabolomic analysis was performed by Ultrahigh Performance Liquid Chromatography-Tandem Mass Spectroscopy (UPLC-MS/MS), with support from the Houston Omics Collaborative.Results and discussionAmino acid metabolism was the primary altered super pathway in DMD followed by carbohydrate metabolism and lipid metabolism. In contrast, BMD and LGMD 2A exhibited a more prominent alteration in lipid metabolism followed by amino acid metabolism. In SCAs, primarily lipid, amino acid, peptide, nucleotide, and xenobiotics pathways are affected. Our findings offer new insights into the variance of metabolite levels in MD and SCA, with substantial implications for pathology, drug development, therapeutic targets and clinical management. Intriguingly, this study identified two novel metabolites associated with SCA. This pilot cross-sectional study warrants further research involving larger groups of participants, to validate our findings.